Pengaruh Attitude Towards Platfrom Shopee Dan Electronic Word Of Mouth (E-Wom) Terhadap Minat Beli Generasi Z : The Influence of Attitudes Towards the Shopee Platform and Electronic Word of Mouth (E-WOM) on Generation Z's Purchasing Interest - Nabila Salsabila; Tri Lestari (CV Warnak Johanna Nusantara, 2025)
The development of digital technology has changed people's consumption patterns, especially among Generation Z who were born and raised in the digital era. E-commerce is one of the fastest growing sectors, with Shopee being one of the most popular platforms in Indonesia. However, there is still a gap in understanding how attitude towards the platform and electronic word of mouth (e-WOM) affect Generation Z's purchase intention. This study aims to analyze the influence of attitude towards the Shopee platform and e-WOM on Generation Z's purchase intention. The method used in this research is a survey by distributing questionnaires to 80 respondents who are active Shopee users. The data collected was analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method to test the relationship between variables. The results showed that a positive attitude towards the Shopee platform had a significant effect on purchase intention, with a T-statistic value of 3,764 and a P-value of 0.000. In addition, e-WOM also has a positive and significant effect on purchase intention, with a T-statistic of 2.497 and a P-value of 0.013. Simultaneously, these two variables explain 27.3% of the variation in Generation Z's purchase intention. These findings provide important implications for Shopee managers to continuously improve user experience and utilize e-WOM as a marketing strategy.